RELATIONSHIP BETWEEN HUMAN AND ENVIRONMENT USING ECOCRITICISM IN THE LEGACY OF HEOROT NOVEL BY LARRY NIVEN, JERRY POURNELLE, AND STEVEN BARNES - Theodorick Ardavid Manullang; Singgih Daru Kuncara; Fatimah Muhajir (Prosiding Seminar Nasional Bahasa, Sastra, dan Seni (Sesanti), 2021)
This research deals with the relationship between human and environment as seen in The Legacy Of Heorot Novel by Larry Niven, Jerry Pournelle, and Steven Barnes. The purpose of this research is to find out the relation between humans and the environment that affect the ecology of Avalon. This research uses qualitative method and ecocriticism theory by Greg Garrad. The theory of pastoral, wilderness, and the animal are used to analyze the relationship between human and environment and the behavior of main character towards nature. The result of this research shows that there are several relationships between human and the environment in the novel. The relationship that shows in the novel such as overhunting towards wild animal and land consumption that leads to the destruction of wild animal habitat, wild animal extinction, and overpopulation of other wild animals. Meanwhile, the main character shows his behavior towards nature to re-establish the ecology from his speech such as telling people on Avalon to stop building human settlement, prohibit overhunting activity, and reducing the overpopulated wild animal. The main character also shows his behavior from his action such as killing overpopulated Grendel using electric fence, deadfall trap, and controlling Grendel’s territory and population.